Case report: Expansion of phenotypic and genotypic data in TENM3-related syndrome: Report of two cases - Lu, Fen; Xu, Xin; Zheng, Bixia; Wang, Chunli; Zhou, Wei; Tang, Jian; Zhao, Xiaoke (Frontiers in Pediatrics, 2023)
Biallelic TENM3 variants were recently reported to cause non-syndromic microphthalmia with coloboma-9 (MCOPCB9) and microphthalmia and/or coloboma with developmental delay (MCOPS15). To date, only eight syndromic and non-syndromic microphthalmia cases with recessive TENM3 variants have been reported. Herein, we report two unrelated new cases with biallelic variants in TENM3, widening the molecular and clinical spectrum. Regarding patient 1, WES revealed compound heterozygous variants in the TENM3 gene: c.3847_3855del; p.Leu1283_Ser1285del and c.3698_3699insA; p.Thr1233Thrfs*20 in the index patient, who was presenting with bilateral microphthalmia, congenital cataract, microcephaly, and global developmental delay. Regarding patient 2, compound missense heterozygous variants in the TENM3 gene were identified: c.941C > T; p.Ala314Val and c.6464T > C; p.Leu2155Pro in the 3-year-old boy, who presented with congenital esotropia, speech delay, and motor developmental delay. The clinical features of these two cases revealed high concordance with the previously reported cases, including microphthalmia and developmental delay. The presence of microcephaly in our patient potentially expands the neurologic phenotype associated with loss of function variants in TENM3, as microcephaly has not previously been described. Furthermore, we present evidence that missense variants in TENM3 are associated with similar, but milder, ocular features.